The Role Of Social Media In Modern Day Marketing - Amir, Mustafa Amir Hassan; Basalamah, Muhammad Ridwan; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract Social media provides wider access to a global audience at relatively low costs compared to traditional media advertising. The aim of this research is to identify the factors that influence the success of a social media-based marketing strategy in the context of modern marketing and to understand the constraints or challenges faced by companies in developing and implementing effective marketing strategies via social media. The method used in this research is descriptive qualitative. Results  A deep understanding of the target audience is crucial for designing relevant and engaging content, which can increase engagement and build stronger relationships with consumers. High-quality content and diversification of content types help attract attention and sustain audience interest. Selecting the appropriate social media platform ensures that the company can reach the right audience with their marketing objectives.  Conclusion  The research concludes that facing negative feedback and reputation crises, gaps in understanding and technological skills, changes in consumer behavior, as well as strict privacy regulations and policies, are essential challenges that need to be addressed. Keywords: Social Media, Marketing, Online